2010
DOI: 10.2478/v10032-010-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Mi23 Marker and the Potato Aphid Biology as Indicators of Tomato Plant (Solanum lycopersicum L.) Resistance to Some Pests

Abstract: SummaryMi-1.2 gene, expressed in tomato plants, contributes to endogenous resistance against nematodes and some Hemiptera insects. The aim of this study was to screen the presence of dominant/recessive locus of the Mi-1.2 gene in tomato cultivars with different allelic combination using Mi23 SCAR method and to assess the capacity of the local potato aphid (Macrosiphum euphorbiae Thomas) population to develop on different tomato cultivars (dominant and recessive homozygotes in Mi-1.2 locus). The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, Mi-1.2 gene cannot be a satisfying source of plant resistance to this mite-herbivore generalist. However, dominant Mi-1.2 gene homozygously expressed in tomato plants may contribute to the endogenous resistance to M. euphorbiae (Kaloshian et al 1995, Rossi et al 1998, Goggin et al 2001, 2004, Godzina et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Mi-1.2 gene cannot be a satisfying source of plant resistance to this mite-herbivore generalist. However, dominant Mi-1.2 gene homozygously expressed in tomato plants may contribute to the endogenous resistance to M. euphorbiae (Kaloshian et al 1995, Rossi et al 1998, Goggin et al 2001, 2004, Godzina et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…When Mi-1.2 gene is expressed in plants it may contribute to the endogenous resistance to three nematode species (Meloidogyne incognita, M. javanica, M. arenaria) and some Hemiptera insects (Macrosiphum euphorbiae, Bemisia tabacci, Bactericerca cockerelli) as well (Kaloshian et al 1995, Rossi et al 1998, Goggin et al 2001,2004, Jiang et al 2001,2003, Casteel et al 2006, Godzina et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Williamson et al (1994) created CAPS (Cleaved Amplification Polymorphic Sequences) marker REX-1 useful in material selection with resistance to nematode (Meloidogyne spp). Garcia et al (2007) developed co-dominant SCAR (Sequence Characterized Amplified Region) marker Mi23 linked with Mi-1.2 gene (Godzina et al 2010). Kaloshian et al (1995) reported that Mi gene conferring to nematode resistance is tightly linked with Meu-1 gene responsible for resistance to potato aphid (Macrosiphum euphorbiae) in tomato.…”
Section: Nematodesmentioning
confidence: 99%